Atom‐Economic Alk(en)ylations of Esters, Amides, and Methyl Heteroarenes Utilizing Alcohols Following Dehydrogenative Strategies. Issue 3 (10th February 2021) - Donthireddy, S. N. R.; Tiwari, Chandra Shekhar; Kumar, Shashi; Rit, Arnab
Abstract: Owing to the atom‐economic and greener nature, borrowing hydrogen (BH) and acceptorless dehydrogenative coupling (ADC) processes have drawn significant attentions of the researchers across the globe and thus, these strategies have been extensively utilized in synthetic chemistry to access various challenging and valuable compounds. During the last decade, significant progress has been witnessed in the utilization of these protocols involving alkylation of amides/esters/N‐heteroarenes by replacing the traditionally utilized mutagenic reagents as alkyl source with the sustainable biomass derived alcohols under BH/ADC process. This progress includes mainly the transition metal based catalytic systems although a few metal‐free protocols are reported. In this minireview, the advancement from 2010 until September 2020 in accessing C‐alk(en)ylated compounds from the unactivated amides/esters/N‐heteroarenes utilizing alcohols via BH/ADC strategy is highlighted. Additionally, a few reports on aldehydes instead of alcohols as coupling partners are also discussed. Abstract : The amide/ester/N‐heteroarene derivatives are valuable compounds in synthetic and biological chemistry. During the last decade, significant progress has been achieved for the α‐alkylation of these molecules using sustainable biomass derived alcohols under the BH/ADC process. This minireview highlights the advancements (from 2010 until September 2020) in this area to access diverse C‐alk(en)ylated amides/esters/N‐heteroarenes utilizing alcohols as potential alkylating agents.